An automated enzymatic method for measurement of D-arabinitol, a metabolite of pathogenic Candida species. - Switchenko, A C (1994)
An automated enzymatic method was developed for the measurement of D-arabinitol in human serum. The assay is based on a novel, highly specific D-arabinitol dehydrogenase from Candida tropicalis. This enzyme catalyzes the oxidation of D-arabinitol to D-ribulose and the concomitant reduction of NAD+ to NADH. The NADH produced is used in a second reaction to reduce p-iodonitrotetrazolium violet (INT) to INT-formazan, which is measured spectrophotometrically. The entire reaction sequence can be performed automatically on a COBAS MIRA-S clinical chemistry analyzer (Roche Diagnostic Systems, Inc., Montclair, N.J.). Replicate analyses of human sera supplemented with D-arabinitol over a concentration range of 0 to 40 microM demonstrated that the pentitol could be measured with an accuracy of +/- 7% and a precision (standard deviation) of +/- 0.4 microM. Serum D-arabinitol measurements correlated with those determined by gas chromatography (r = 0.94). The enzymatic method is unaffected by L-arabinitol, D-mannitol, or other polyols commonly found in human serum. Any of 17 therapeutic drugs potentially present in serum did not significantly influence assay performance. Data illustrating the application of the assay in patients for possible diagnosis of invasive candidiasis and the monitoring of therapeutic intervention are presented. The automated assay described here was developed to facilitate the investigation of D-arabinitol as a serum marker for invasive Candida infections.